How does the closure of interorganizational relationships affect entrepreneurial orientation? - Maria José Ruiz-Ortega; Gloria Parra-Requena; Pedro Manuel García-Villaverde; Job Rodrigo-Alarcon (BRQ Business Research Quarterly, 2017)
This study delves in the controversy about the nature and the sign of the effect of interorganizational relationships on entrepreneurial orientation. The paper analyses the effects of networks of interorganizational relationships at firm level. Specifically, we study the influence of closure of interorganizational relationships in entrepreneurial orientation and the mediating role of dynamic capabilities. The empirical analysis was developed on a sample of 292 Spanish agri-food firms. We detect a positive mediating effect of the closure of interorganizational relationships, mainly cooperative relationships, on entrepreneurial orientation through dynamic capabilities. It highlights the emergence of a suppression effect uncovering the dark side of closed interorganizational relationships in several dimensions of entrepreneurial orientation – proactiveness, autonomy and risk-taking –. This paper contributes to link three theoretical approaches – social capital, entrepreneurship and dynamic capabilities – to probe further into the implications of interorganizational relationships."
Keywords: 650; Interorganizational relationships; Closure; Entrepreneurial orientation; Dynamic capabilities; Suppression effect